2021
DOI: 10.1080/02508060.2021.1940715
|View full text |Cite
|
Sign up to set email alerts
|

Exploring water access in rural Kenya: narratives of social capital, gender inequalities and household water security in Kitui county

Abstract: Access to water and sanitation as a basic human right is still limited within resource-poor rural settings of Africa, including Kitui, Kenya. This is exacerbated by prevailing gender inequalities which can be mediated when communities leverage on social capital. Qualitative methods were used to examine how values embedded in social capital enable women and vulnerable groups to cope with household water insecurity. How communities exploit the bonding and bridging dimensions of social capital to cope with water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…For example, voice strategies take the form of complaints, demonstrations, and the formation of associations to help address water supply challenges. They include engaging in collective action (Bisung, 2021; Bukachi et al, 2021; Bulled, 2018; Kelly et al, 2017; Patrick, 2021). For this to occur, individuals need to hold sufficient agency, power, and social capital.…”
Section: Results—climate Change Water and Women: Complex Interlinkagesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, voice strategies take the form of complaints, demonstrations, and the formation of associations to help address water supply challenges. They include engaging in collective action (Bisung, 2021; Bukachi et al, 2021; Bulled, 2018; Kelly et al, 2017; Patrick, 2021). For this to occur, individuals need to hold sufficient agency, power, and social capital.…”
Section: Results—climate Change Water and Women: Complex Interlinkagesmentioning
confidence: 99%
“…Households can also adapt to water inaccessibility through “exit strategies” by finding, and potentially treating, alternate water sources. Some of these include water sharing, recycling water, increasing water storage capacity, using alternative sources including bottled/sachet water, and migrating to meet their needs (Arku et al, 2015; Asoba et al, 2019; Bernard & Joyfred, 2020; A. Brewis et al, 2021; Bukachi et al, 2021; Dickin et al, 2011; Emenike et al, 2017; Hamlet et al, 2021; Hofstetter et al, 2008; Jeil et al, 2020; Majuru et al, 2018; Marcatelli, 2013; Mushavi et al, 2020; Newcomer et al, 2017; Ngwenya & Kgathi, 2006; C. Nounkeu et al, 2019; Patrick, 2021; Pearson et al, 2017; Pearson et al, 2021; Schlamovitz & Becker, 2021; Twisa & Buchroithner, 2019; Venkataramanan et al, 2019; Walker, 2019; Yillia et al, 2021). Unsurprisingly, in Mozambique, Van Houweling (2016) found that during the long dry season, nearby wells and streams often dry up, forcing water fetchers to travel greater distances to alternative sources to obtain water.…”
Section: Results—climate Change Water and Women: Complex Interlinkagesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt, for instance, El Didi and Corbera (2017) found that elites guided by this hadith construct public wells ( sobal ) to provide water to others. Although many other studies find that people affirm an obligation to give water—usually implicitly—because water is essential to life (Buckaki et al, 2021a, 2021b; Drew, 2019; Estes, 2017; Harris et al, 2020; McIvor, 2020; Wutich, 2011; Wutich et al, 2018), water sharing research thus far has not explicitly investigated the mechanisms of social pressure (or lack thereof) that people may use to enforce morally understood obligations to share water. Though, many studies indicate that people do attempt to pressure others into sharing water (Drew et al, 2021; Schnegg, 2015; Schnegg & Linke, 2015; Schnegg et al, 2016; Wutich et al, 2022).…”
Section: Advancing Theory On Moral Economies For Water: Future Direct...mentioning
confidence: 99%
“…Additionally, the incidence of diarrhea was higher in households experiencing water insecurity and the difference was statistically significant. Our study specifically focused on drinking water access, but other previous studies have shown that water insecurity has been associated with domestic violence [42]; food insecurity [10,43]; depression and anxiety [44,45] and limited social capital [46].…”
Section: Plos Watermentioning
confidence: 99%